Capital and liquidity ratios and financial distress. Evidence from the European banking industry. Issue 2 (March 2017) - Chiaramonte, Laura; Casu, Barbara
Abstract: Using a large bank-level dataset, we test the relevance of both structural liquidity and capital ratios, as defined in Basel III, on banks' probability of failure. To include all relevant episodes of bank failure and distress (F&D) occurring in the EU-28 member states over the past decade, we develop a broad indicator that includes information not only on bankruptcies, liquidations, under receivership and dissolved banks, but also accounts for state interventions, mergers in distress and EBA stress test results. Estimates from several versions of the logistic probability model indicate that the likelihood of failure and distress decreases with increased liquidity holdings, while capital ratios are significant only for large banks. Our results provide support for Basel III's initiatives on structural liquidity and for the increased regulatory focus on large and systemically important banks.